2001
DOI: 10.1007/pl00014585
|View full text |Cite
|
Sign up to set email alerts
|

Surgical therapy for lumbar spinal stenosis: evaluation of 300 cases

Abstract: Although lumbar spinal stenosis syndrome is extremely common, considerable controversy continues to surround its classification, diagnosis, and treatment. In this article, we retrospectively analyzed the clinical, radiological, and surgical characteristics of 300 patients operated on in our clinics with the diagnosis of lumbar spinal stenosis. Surgical therapy and outcome are discussed with respect to the known facts. After clinical and radiological evaluation, 300 patients were diagnosed with lumbar spinal st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The Spine Patient Outcomes Research Trial, the largest study of its kind, showed that patients with symptomatic spinal stenosis compared to those treated nonoperatively maintained greater improvement in pain and function through 4 years. Traditionally, standard decompressive procedures[ 8 9 10 ] involve total laminectomies and extensive removal of the accompanying spinous processes and posterior arches. However, microscopic interlaminar decompression involves focused decompression between adjacent laminae, with the spinous processes, and their attaching muscles kept intact.…”
Section: Discussionmentioning
confidence: 99%
“…The Spine Patient Outcomes Research Trial, the largest study of its kind, showed that patients with symptomatic spinal stenosis compared to those treated nonoperatively maintained greater improvement in pain and function through 4 years. Traditionally, standard decompressive procedures[ 8 9 10 ] involve total laminectomies and extensive removal of the accompanying spinous processes and posterior arches. However, microscopic interlaminar decompression involves focused decompression between adjacent laminae, with the spinous processes, and their attaching muscles kept intact.…”
Section: Discussionmentioning
confidence: 99%
“…14 Kalbarczyk and colleagues 13 performed a laminectomy accompanied by bilateral medial facetectomy in 70% of their patients with lumbar spinal stenosis. Cirak et al 6 concluded that in cases of lumbar spinal stenosis, decompressive laminectomy and extensive foraminotomy without instrumentation have good outcomes. Galiano and coworkers 10 showed that in the long term, decompressive laminectomies in selected octogenarians resulted in decreased disability, decline of analgesic use, and increased quality of life.…”
Section: Methods Of Decompression and Outcomementioning
confidence: 99%
“…Further long-term studies have demonstrated superior outcomes after surgery than after conservative management. 6 …”
Section: Conservative Versus Surgical Treatmentmentioning
confidence: 99%
“…The secondary development of degenerative changes that further narrow the lumbar spinal canal precipitated symptoms. 2 Lumbar spinal canal stenosis now is an accepted clinical entity. The symptoms and signs are due to narrow canal space.…”
Section: Introductionmentioning
confidence: 99%